Clinical use of linguistic discourse analysis for the assessment of language in aphasia. Issue 10 (3rd October 2017) - Bryant, Lucy; Spencer, Elizabeth; Ferguson, Alison
ABSTRACT: Background : Linguistic discourse analysis is an assessment method widely applied within aphasia research literature to examine impairments as they affect the language of daily function—discourse. Although this literature suggests that clinical applications do occur, it also identifies barriers that may inhibit the translation of research to practice. Aims : This study aimed to identify the frequency of use and methods of linguistic discourse analysis application by speech pathologists when assessing their clients with aphasia. Methods & Procedures : A survey was distributed electronically to speech pathologists in five English-speaking countries using the online survey management tool Survey Monkey®. Clinical applications of linguistic discourse analysis were examined using descriptive statistics and cross-tabulation analyses. Outcomes & Results : Of 123 valid survey results, 106 clinicians reported use of linguistic discourse analysis to assess language in aphasia. Respondents collected language elicited in conversational contexts and expositional discourse samples most often, and subjected these samples to a range of linguistic measures. Most clinicians applied a judgement-based method of analysis based on clinical observation. Clinicians reported positive attitudes towards the use of linguistic discourse analysis, but were limited from widespread use by barriers such as a lack of available clinical time. Conclusions : Results revealed that speech pathologists defined and therefore implemented linguistic discourse analysis in a variety of ways. The methods used to elicit, prepare and analyse discourse varied among respondents. Further investigation is warranted to examine the effectiveness of clinical discourse analysis applications and to support the translation of evidence-based research methods to clinical practice.